ANALISIS PENGENDALIAN BIAYA PRODUKSI DAN PENGARUHNYA TERHADAP LABA PABRIK PT ‘X’ DI SUMATERA BARAT - Ningsih, Radna; Armen, Armen; Triyani, Wulan (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2017)
The purpose of this study was to determine the production costs are budgeted by PT “X” has budgeted appropriately. And to know the control of production costs and the impact on grossprofit of an enterprise, then provide solutions (recommendations / fixes) to the problem that makes the allocation and control of production costs are less efficient and effective. The method of analysis used in this study is to use the analysis of the reports of the production cost in the form of raw material costs, labor costs and factory overhead costs and use the budget report production costs by using the analysis in 2010 and 2011. The results of this research can be considered the company to be more concerned with the allocation of the cost of production and the right to control the cost of production in order to achieve maximum profit for the company. Recommendations can be given as corrective measures can be taken to fix the problems the company is monitoring the company must keep records of the cost of production in order to avoid further mistakes cost allocation and corporate presentation can further improve the control of production costs to profits by arranging periodic activity reports so that companies can get more optimal profits and had to check periodically to record the presentation of the allocation of costs in order to obtain maximum gross profit.